Design modifications and comparative study of different biomass cookstoves - Rana, Karmvir Singh (My University, 2013)
In the developing countries including India most of the population lives in rural areas depends on biomass especially wood, cow dung, charcoal, etc., for cooking purposes. Approximately half a million premature deaths and nearly 500 million cases of illness are estimated to occur annually as a result of exposure to smoke and harmful emissions coming from biomass combustion. As per World Health Organization (WHO) report, indoor air pollution is the third leading health risk affecting the people directly and indirectly especially, women and female children in the rural areas around the globe. In order to address the above said problems associated with traditional cookstove models available to the common people, few cookstove models were designed and fabricated during this study. The designed cookstove models include, the modified traditional and improved cookstoves, besides, other models available in the market. The concept of energy and exergy analysis was applied to all the models and following conclusions are made: • The energy, exergy efficiencies and power output of the modified traditional cookstove (NIRE-02) were found to be the highest with top spacing. However, it was found that this cookstove model exhibits the best performance when grate with top spacing is provided. • The maximum value of energy efficiency, exergy efficiency and power output was found for the improved (NIRE-03) model with optimum insulation without wick. • The analysis for emission exhibits that the improved cookstove model reduces 2.45 Ton of CO2/household/year while, it was found to be 2.1 Ton in the case of the modified traditional model. • It was also found that both the models (NIRE-02 model and NIRE-03) exhibit better performance than those of the traditional cookstove models being used by the common public in the country. • Also the improved cookstove model (NIRE-03) exhibits better combustion and higher performance than that of the modified traditional cookstove (NIRE-02). • When the different wood samples were evaluated by proximate, ultimate and Thermo-gravimetric analysis, mixed results were obtained but sagwan (tectona grandis) exhibits the better results than those of the other wood samples (Shhesham, Mango, Eucalyptus, etc.) used in this study.
M.Tech (EST) Dissertation
Keywords: Cookstove; Biomass burning; Wood analysis; CDM